The Role of Heritage Planning in Dark Sites Case Study : Tsunami Sites in Banda Aceh - Zya Dyena Meutia; Arief Rosyidie; Denny Zulkaidi; Sri Maryati (Universitas Teuku Umar, 2020)
The concept of dark heritage has been used as a concept of preserving an area or site that contains relics due to dark events in the past. Tsunami disaster in 2004 that hit Banda Aceh as the most affected area after the disaster has left various relics that need a consideration regarding to dark heritage planning. However, in the planning of dark heritage, it has not yet considered aspects of local communities, especially survivors as the most affected group from the tsunami. The purpose of this paper is to observe the planning of dark heritage involving the community as an important aspect in the preservation of post-disaster areas and to find out the components and values that are considered important by the community in preserving dark heritage. The study was conducted from August 2019 to January 2020 in the post-disaster area, Banda Aceh, as the most affected area using a qualitative approach, a case study. This study showed that dark heritage planning which involves the community is strongly influenced by communicative values in building agreements in the post-disaster memorial area to create sustainable dark heritage planning. Field research also found that spatial elements need to be considered in planning post-disaster dark heritage in seeing post-disaster areas as areas of dark heritage that are also influenced by religious values by the community treating dark heritage sites.